Double Particularity : Karl Barth, Contextuality, and Asian American Theology - Lee, Daniel D. (Book collections on Project MUSE., 2017)
With the center of worldwide Christianity moving to the global South, and even as American Christianity becomes more reflective of immigrant populations, the theological need for a deeper engagement with context is more urgent than ever. Karl Barth, particularly his thought on election, Christology, and reconciliation, offers much wisdom and insight for the churches of the majority world and for these ethnic churches. Hence, this study is a contribution to the development of a connection between Barth and contextual theology, to the stimulation and enrichment of both.